Analysis Of Business Development Strategy In Improving The Welfare Of Grape Cultivationers From An Islamic Economic Review (Case Study At Jagad Farm Binjai) - Nursafira, Adela; Arif, Muhammad; Syahriza, Rahmi (Universitas Ibn Khladun Bogor, 2025)
Particularly in the development of grape cultivation businesses that consider Islamic economic values. However, an Islamic economic approach is highly relevant for application in agribusiness, as it emphasizes justice, blessings, sustainability, and welfare. This research uses a qualitative approach and uses a case study. The aim is to analyze the grape cultivation business development strategy at Jagat Farm Binjai and assess its alignment with Islamic economic principles. Primary data was obtained through interviews with business owners and other relevant parties, while secondary data was collected from literature, including books, journals, and theses from previous researchers related to grape cultivation and Islamic economics.Based on the various aspects discussed, it can be concluded that the development of a grape cultivation business at Jagad Farm Binjai has significant potential to improve the welfare of farmers and support the local economy. The implemented strategy integrates Islamic economic principles and optimizes strengths such as product quality and processing innovation, while addressing weaknesses such as a lack of technology and trained human resources. Government support and the use of digital platforms also play a crucial role in expanding the market and increasing the competitiveness of this business. By considering internal and external factors, as well as the principles of sustainability and social justice, the development of grape cultivation in Binjai is expected to become a sustainable business model, providing equitable economic and social benefits, and strengthening Indonesia’s position in the future grape agribusiness industry.